False Belief and Harmful Cultural Practices of Chhaupadi System in Nepal - Karki, Tej Bahadur; Khadka, Kalpana (Nepal Journal of Multidisciplinary Research, 2019)
Belief system is strongly associated with the socio-cultural practices, family orientation, social environment, schooling of people. Some of the false belief and harmful practices are associated with the Chhaupadi system of Nepal. Chhaupadi is a social tradition related to "menstrual taboo" in the western part of Nepal for Hindu women, which prohibits them from participating in normal family activities during a menstruation period, as they are considered "impure". The main aim of this study is to identify the false belief and harmful cultural practices of Chhaupadi system in Nepal. The study was conducted among the girl students of grade 9 and 10 by using the structured questionnaire survey. The study found that there are many false belief system and harmful cultural practices were associated with Chhaupadi system. The menstrual women were not allowed to enter into the kitchen, not allowed to cook food, not allowed to touch the drinking water, not allowed to enter into the religious places and not allowed to participate in the social functions. The false belief system and harmful cultural practices had negatively affected in the health and hygiene and personal and professional growth and development of women and girls, so such belief system and practices should be removed from the society though the series of orientation and wider level of community discussion.